Periostin and its interacting proteins in the construction of extracellular architectures - Kii, Isao; Ito, Harumi (Cellular and molecular life sciences : CMLS, 2017)
Periostin is a matricellular protein that is composed of a multi-domain structure with an amino-terminal EMI domain, a tandem repeat of four FAS 1 domains, and a carboxyl-terminal domain. These distinct domains have been demonstrated to bind to many proteins including extracellular matrix proteins (Collagen type I and V, fibronectin, tenascin, and laminin), matricellular proteins (CCN3 and βig-h3), and enzymes that catalyze covalent crosslinking between extracellular matrix proteins (lysyl oxidase and BMP-1). Adjacent binding sites on periostin have been suggested to put the interacting proteins in close proximity, promoting intermolecular interactions between each protein, and leading to their assembly into extracellular architectures. These extracellular architectures determine the mechanochemical properties of connective tissues, in which periostin plays an important role in physiological homeostasis and disease progression. In this review, we introduce the proteins that interact with periostin, and discuss how the multi-domain structure of periostin functions as a scaffold for the assembly of interacting proteins, and how it underlies construction of highly sophisticated extracellular architectures.